Value of a Statistical Life: Relative Position vs. Relative Age - Kniesner, Thomas J; Viscusi, W. Kip (American Economic Review, 2005)
by the Harvard Olin Center for Law, Economics, and Business. 1 The value of a statistical life (VSL) plays the central role in regulatory decisions affecting risks to life and health. Economists continue to try to improve the accuracy and concomitant usefulness of benefit assessments by examining whether the typically calculated VSL understates the average benefits of life-saving government regulations and whether the heterogeneity in individual VSLs should influence policy. Here we examine empirically the importance of two possible omitted variables that could affect the estimates of VSL based on the typical wage equation, relative position in the wage distribution and relative age within the life-cycle pattern of consumption. We find that ignoring the worker’s relative position in the wage distribution does not affect VSL as conventionally computed, but that ignoring workers ’ planned consumption undervalues VSL by perhaps 20 percent. Our results have implications for the economic understanding of the compensating wage differential process as well as for policy. The modest effect of adding measures of relative economic position to the canonical hedonic wage regression suggests that workers taking risky jobs make their decisions based on their personal wage-risk tradeoff rather than their status or relative economic position. In contrast, the worker’s relative position within the personal life cycle pattern of consumption is a driving force that affects the temporal trajectory of VSLs over the life cycle and is a promising way to consider distributional consequences of policy simply. Appropriate VSL assessments should not downweight the risks to older citizens compared to the young because the effect of age on the level of planned consumption may outweigh or dampen the effect of age in shortening people’s remaining future lifetimes. 2